Religious Doubts and Sleep Quality: Findings from a Nationwide Study of Presbyterians #090709revised - Ellison, Christopher G. (Review of religious research, 2011)
A growing literature examines the correlates and sequelae of spiritual struggles, such as religious doubts. To date, however, this literature has focused primarily on a handful of mental health outcomes (e.g., symptoms of depression, anxiety, negative affect), while the possible links with other aspects of health and well-being, such as poor or disrupted sleep, have received much less attention. After reviewing relevant theory and previous studies, we analyze data from a nationwide sample of Presbyterian Church (USA) members to test the hypothesis that religious doubts will be inversely associated with overall self-rated sleep quality, and positively associated with the frequency of sleep problems and the use of sleep medications. We also hypothesize that part of this association will be explained by the link between religious doubts and psychological distress. Results offer moderate but consistent support for these predictions. We end with a discussion of the implications of these findings, a brief mention of study limitations, and some suggestions for future research.